2020
DOI: 10.1139/cjz-2019-0155
|View full text |Cite
|
Sign up to set email alerts
|

Body condition of spring-migrating Green-winged Teal (Anas crecca)

Abstract: Spring migration is an energetically demanding event that can impact nutrient dynamics of individuals during the breeding season through carry-over effects. Limited food availability at spring stopover areas may have cross-seasonal effects that adversely impact waterfowl populations. We collected 161 Green-winged Teal (Anas crecca Linnaeus, 1758; hereafter Teal) throughout the Illinois River Valley, USA, during February–April of 2016–2018 and estimated body condition using three condition indices (scaled mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 87 publications
0
15
0
Order By: Relevance
“…We used contemporary, unbiased methods to quantify food selection of spring-migrating teal within a migration stopover region in the Midwest, USA. Consistent with the spring dietshift hypothesis (Klimas et al 2020;Hitchcock et al 2021), we hypothesized that teal would select invertebrates within the Illinois River Valley during spring migration. Additionally, we hypothesized that selection of food items would be impacted by wetland to river connectivity due to the influence of floodplain inundation on vegetative communities during the growing season.…”
Section: Introductionmentioning
confidence: 81%
See 4 more Smart Citations
“…We used contemporary, unbiased methods to quantify food selection of spring-migrating teal within a migration stopover region in the Midwest, USA. Consistent with the spring dietshift hypothesis (Klimas et al 2020;Hitchcock et al 2021), we hypothesized that teal would select invertebrates within the Illinois River Valley during spring migration. Additionally, we hypothesized that selection of food items would be impacted by wetland to river connectivity due to the influence of floodplain inundation on vegetative communities during the growing season.…”
Section: Introductionmentioning
confidence: 81%
“…We tested for differences in selection intensity among age, sex, year, migratory period, and wetland connectivity variables. To control for potential differences in body condition during the spring migration period (Klimas et al 2020), we identified the average peak spring migration date (~15 March) for teal in the IRV using eBird data from 2016-2018 and classified collections as early (before 15 March) or late (on or after 15 March; eBird 2019). We categorized wetland connectivity with the main channel of the Illinois River as 1) directly connected or influenced by the Illinois River below flood stage (connected), 2) influenced by the river at or above moderate flood stage (partially connected), and 3) disconnected via surface water and mostly uninfluenced by the Illinois River (isolated; Lemke et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations